Bridging neuro-biomarkers and MR imaging: The synergistic role of glial fibrillary acidic protein in early CNS disease diagnosis - Mohammad Ghaderian; Daryoush Shahbazi-Gahrouei; Safoora Nikzad; Elnaz Didehban; Hossein Hafezi; Ismail Laher; Fahime Hossein Beigi; Saghar Shahbazi-Gahrouei; Tahereh Boustani (IBRO Neuroscience Reports)
Molecular neuroimaging is a powerful and emerging tool for the early detection and monitoring of central nervous system (CNS)-related and neurodegenerative diseases. Biomarkers play a crucial role in diagnostic accuracy, prognosis, and treatment efficacy. Among these, Glial Fibrillary Acidic Protein (GFAP), a cytoskeletal intermediate filament protein, serves as a key indicator of astrocytic activation and neuroaxonal injury. Elevated levels of GFAP in cerebrospinal fluid (CSF) and blood-based samples (serum/plasma) are increasingly recognized as potential biomarkers for neurodegeneration and CNS pathology. Advanced molecular imaging techniques, including Diffusion Tensor Imaging (DTI) and Diffusion-Weighted Imaging (DWI), along with conventional magnetic resonance imaging (MRI), provide visual scoring, local morphometry, and volumetric analysis. Therefore, integrating GFAP with neuroimaging modalities offers the potential to improve disease characterization, allowing for accurate spatial mapping of neurodegeneration and monitoring of disease progression at a molecular level. The relationship between MRI and GFAP is currently under evaluation. This review explores the interplay between GFAP and molecular neuroimaging, highlighting their combined potential to enhance early diagnosis, prognosis, and treatment monitoring of CNS disorders.